Medium-term oncological outcome endoscopic surgery malignant tumors of the nasal cavity and paranasal sinuses - M. V. Bolotin; A. M. Mudunov; A. E. Raportinova; D. A. Peshko (Опухоли головы и шеи, 2024)
Introduction. Transnasal endoscopic resection of sinonasal tumors is currently used in many clinics around the world. Short- and long-term oncological outcomes primarily depend on tumor histology. However, most currently existing studies are based on a small number of observations due to the rarity and heterogeneity of sinonasal malignancy.Aim. To evaluate short- and medium-term oncological outcomes of treatment of malignant sinonasal tumors. Materials and methods. The study is based on retrospective analysis of 95 patients who underwent endoscopic surgery for sinonasal malignancy between 2014 and 2023 at the N.N. Blokhin National medical Research Center of Oncology. Squamous cell carcinoma was diagnosed in 27 (28.4 %) patients, olfactory neuroblastoma in 13 (13.7 %), mucosal melanoma in 30 (31.6 %), adenocarcinoma in (6.3 %), adenoid cystic carcinoma in 7 (7.3 %), sarcomas in 12 (12.7 %). Results. In the study group, 2-years overall survival and recurrence-free survival were 81.3 and 61.4 % respectively, survival without local recurrence was 87.5 %. The outcomes significantly depended on tumor histology.Conclusion. Oncological outcomes of endoscopic resections of sinonasal tumors significantly depend on tumor histology, but in general they allow to achieve good local control. Small number of observations, variety of histological forms, and short follow-up periods do not allow to accurately evaluate the effectiveness of this approach for each tumor type. further research in large populations is needed to establish risk factors.